Deux séries chrysostomiennes : Sur l’impuissance du diable et Sur l’obscurité des prophéties - Peleanu, Adina (Revue d'études augustiniennes et patristiques, 2011)
Since the publication of the 1718 edition of B. de Montfaucon, the scholarly consensus on St John Chrysostom has been that the De diabolo tentatore homilies (CPG 4332) belong together as a homogenous series of three discourses. However, an in-depth study of these texts, together with an analysis of the manuscript tradition and of the Catalogue Augustanus, demonstrated the need to reconsider the composition of the De diabolo tentatore series, which we re-named here as On the impotence of the devil. Thus the first homily within the On the impotence of the devil series also features as the third homily within the On the obscurity of prophecies series (CPG 4420). These two sequences, which are well established, are also well defined and delineated, both thematically and chronologically. The problem that remains is the possibility of establishing whether the two series of homilies were delivered at approximately the same time. The series On the obscurity of prophecies would have been delivered in the course of the Lent of the year 386, right at the beginning of St John’s priestly ministry. It is also certain that the two homilies On the impotence of the devil were given in Antioch, in the course of the Bright Week, at the time of the bishopric of Flavian. We have no indication regarding the dates when the two sermons were preached. The absence of any further manuscripts in continuation of these five homelies strongly suggests the hypothesis that the two groups of sermons would have been delivered on different dates and that we are dealing here with two distinct series of homelies.